(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article discusses the role of agritourism in urban sustainability, The rapid expansion of urbanization has distanced cities from their rural roots, yet agritourism offers a pathway to reconnect these realms within modern urban planning. This paper examines the integration of agritourism—encompassing urban farming, local food production, and agricultural experiences—into city landscapes as a strategy for sustainable development